The impact of bank profitability on the degree of banking security (Case study of Bemo Saudi Fransi Bank, which is listed on the Damascus Stock Exchange) - الشريف ياسمين; نهاد نادر; لينا حسن فياض (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The study aimed primarily to demonstrate the impact of profitability (rate of return on assets and rate of return on equity) on the banking security of Bemo Bank listed on the Damascus Stock Exchange in Syria. The researcher used the deductive approach to test the impact of profitability (rate of return on assets and rate of return on equity) on banking security in the bank under study in Syria. In order to conduct the practical study and test the research hypothesis, the researcher used a survey research design and a secondary data tool on private banks. Financial data was collected from the selected banks, such as return on equity and total assets. As for statistical methods: the SPSS program (20) was used to prove or deny the hypothesis of the research. A significance level of 5% was used, that is, testing hypotheses at a confidence level of 95%. The study reached results including: There is a statistically significant effect of the rate of return on assets on the banking security of BIMO Bank listed on the Damascus Stock Exchange in Syria. There is a statistically significant effect of the rate of return on equity on the banking security of BIMO Bank listed on the Damascus Stock Exchange. In Syria, there is no statistically significant effect of profitability on the banking security of Bemo Bank listed on the Damascus Stock Exchange in Syria.